The Usefulness of Argon Plasma Coagulation Technique for Preventive Consolidation Therapy of Esophageal Varices - Kato, Keizo; Kikuchi, Yasuharu (Japanese Journal of Portal Hypertension, 2002)
Argon plasma coagulation (APC) has been widely used for various hemostatic procedures and the treatment of early cancer. In the present study, we used APC as preventive consolidation therapy of esophageal varices and studied its usefulness. Subjects were 13 patients with esophageal varices who had previously received EVL and/or EIS. Results were compared with those of 20 patients who didn't receive the APC treatment (non-APC group). APC was performed twice at an interval of one week with argon flow rate of 2 L/min and high-frequency output of 60 W. Complications were slight chest pain in five and transient low grade fever in nine. Varices were completely disappeared in all patients. Only one patient showed recurrence (F1 RC (+)). The annual cumulative recurrence rate in the APC group was 12.5%, which was significantly lower than that of the non-APC group (61.0%, p=0.03). These results indicate that APC technique as preventive consolidation therapy of esophageal varices is useful, because it shows a preferable safety profile with few complications.